2003
DOI: 10.1167/iovs.03-0455
|View full text |Cite
|
Sign up to set email alerts
|

Postural Stability Changes in the Elderly with Cataract Simulation and Refractive Blur

Abstract: Findings indicate that cataractous and refractive blur increase postural instability, and show why the elderly, many of whom have poor vision along with musculoskeletal and central nervous system degeneration, are at greater risk of falling. Findings also highlight that changes in contrast sensitivity rather than resolution changes are responsible for increasing postural instability. Providing low spatial frequency information in certain environments may be useful in maintaining postural stability. Correcting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
81
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 32 publications
(69 reference statements)
2
81
0
1
Order By: Relevance
“…It has been shown that cataract may cause substantial defects in mobility and orientation, even with a good visual acuity, under low luminance conditions [13,14]. Furthermore, Schwartz et al [15] found that cataract surgery significantly improved postural stability and was cost effective with regard to the high cost of treating fall-related injuries in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that cataract may cause substantial defects in mobility and orientation, even with a good visual acuity, under low luminance conditions [13,14]. Furthermore, Schwartz et al [15] found that cataract surgery significantly improved postural stability and was cost effective with regard to the high cost of treating fall-related injuries in the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…8 A systematic review found that patients who wait more than 6 months for cataract surgery had an increased rate of falls. 9 Furthermore, cataracts have been found to be the most common cause of fracturerelated visual impairment, 10 with untreated cataract causing up to 49% of visual impairment in patients with femoral neck fractures related to decreased vision.…”
mentioning
confidence: 99%
“…12 However, age-related changes in the visual system result in a decline of visual acuity, contrast sensitivity, depth perception, visual field, and adaptation. 13 Visual impairment, measured as well as self-reported, is strongly associated with the risk of falling among older persons, 14 and this relationship is stronger for falls in outdoor environments.…”
Section: Visionmentioning
confidence: 99%